2014
DOI: 10.1161/circep.113.001163
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Contrast for Characterization of Acute Radiofrequency Ablation Lesions

Abstract: Cardiac arrhythmias reflect abnormal electric activity in the heart. Radiofrequency ablation (RFA) is used to treat different arrhythmias by thermally damaging tissue regions and eliminating irregular action potential propagation paths. To ensure a permanent electric block, RFA must create a continuous line of transmural lesions.1 Notwithstanding extensive efforts, the success rates of the RFA operations are still low, 2 likely because of the lack of tools to validate the lesion extent. Current ablation method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 27 publications
4
59
0
Order By: Relevance
“…13 Finally, MRI characterization was only used in the needle ablation group, given the limited availability of MRI, prolonged scanning times (>120 hours), and the fact that previous studies have reported on MRI imaging after conventional ablation, we focused our imaging on the needle group. [19][20][21] The description of conventional ablation lesions on MRI has already been reported, and the sizing of these lesions from gross pathology measurements was shown to be similar and feasible. 21 …”
Section: Limitationsmentioning
confidence: 92%
See 2 more Smart Citations
“…13 Finally, MRI characterization was only used in the needle ablation group, given the limited availability of MRI, prolonged scanning times (>120 hours), and the fact that previous studies have reported on MRI imaging after conventional ablation, we focused our imaging on the needle group. [19][20][21] The description of conventional ablation lesions on MRI has already been reported, and the sizing of these lesions from gross pathology measurements was shown to be similar and feasible. 21 …”
Section: Limitationsmentioning
confidence: 92%
“…[19][20][21] The description of conventional ablation lesions on MRI has already been reported, and the sizing of these lesions from gross pathology measurements was shown to be similar and feasible. 21 …”
Section: Limitationsmentioning
confidence: 92%
See 1 more Smart Citation
“…57 Celik et al performed a detailed study of the characterisation of acute RF lesions using native contrast, performing imaging of left ventricular lesions within 60 min of ablation in 13 pigs. 23 They concluded that it was the higher ferric iron concentration in lesion core that caused a shortening of T 1 -relaxation time, and that this was best exploited using an inversion recovery SSFP sequence. Implementation and clinical validation in humans remains to be established.…”
Section: Acute Lesion Imaging (<4 Hours)mentioning
confidence: 99%
“…4,[7][8][9] Many advances have been introduced to enhance the quality of ablation applications in pulmonary vein isolation such as the use of irrigated and circular diagnostic catheters, 10 3-dimensional tracking systems, robotics, 11 testing with adenosine to reveal dormant conductions, 12 and cardiac magnetic resonance imaging to assess the quality of lesions. 13 Contact force (CF) is a fairly new technology that allows real-time contact feedback between the catheter tip and the targeted cardiac tissue. Theoretically, this approach improves the quality of the lesions and enhances safety outcomes.…”
mentioning
confidence: 99%